DESIGN CHARACTERIZATION OPTIMIZATION OF LENALIDOMIDE-LOADED BOVINE SERUM ALBUMIN NANOPARTICLES FOR MYELOMA THERAPY - BEGUM, SAMEENA; PANDA, NIRANJAN; PRAVEENA, CH. (International Journal of Applied Pharmaceutics, 2026)
Objective: The present investigation focuses on the formulation and optimization of lenalidomide (LD)-loaded bovine serum albumin (BSA) nanoparticles (NPs) using the desolvation method. Box-Behnken design (BBD) was implemented to optimize the formulation. Methods: The desolvation technique was employed to synthesize BSA-NPs encapsulating LD and characterized by particle size analysis, zeta potential, and transmission electron microscopy (TEM) analysis. Results: The findings confirmed that the uniform spherical NPs were formed below 200 nm. Particle size found in the range of 110.9±13.02 nm to 182.8±10.33 nm, entrapment efficiency (EE) found between 60.1±9.01% and 94.80±9.14% and zeta potential-15.3±0.21mV to-29.7 ±0.12mV. A sudden burst release of approximately 55.68% was observed within 4 h from optimized LD BSA NPs (Opt-LD-BSA-NPs), followed by a slower release over 24 h. In vitro, cytotoxicity assays demonstrated selective toxicity against U266 cancer cells. The Opt-LD-BSA-NPs exhibited a significantly lower half-maximal inhibitory concentration (IC50) of 29.70%, indicating enhanced cytotoxic efficacy. Fourier transform infrared spectroscopy (FTIR) and differential scanning calorimetry (DSC) analyses indicated successful drug entrapment and a transition of LD from a crystalline to an amorphous form. The area under curve (AUC) for Opt-LD-BSA-NPs was found to be 22.47 µg/ml/hr, which is 3 times more than the pure LD suspension (6.3025 µg/ml/h). It revealed enhanced bioavailability. Conclusion: These findings underscore the potential of BSA-based nanocarriers to enhance the solubility, stability, and therapeutic efficacy of hydrophobic anticancer agents, such as LD.